"\\frac{d^2y}{dx^2}-2\\frac{dy}{dx}+2y=\\sin 2x"
Let us solve a characteristic equation:
"k^2-2k+2=0"
"(k-1)^2+1=0"
"(k-1)^2=-1"
"k_1=1+i, k_2=1-i"
The general solution is of the following form:
"y(x)=e^x(C_1\\cos x+C_2\\sin x)+y_p(x)," where "y_p(x)" is a particular solution, "C_1, C_2" are arbitrary constants.
The particular solution has the following form:
"y_p(x)=A\\sin 2x+B\\cos 2x", whrere "A" and "B" are constants.
"\\frac{dy_p}{dx}=2A\\cos 2x-2B\\sin 2x"
"\\frac{d^2y_p}{dx^2}=-4A\\sin 2x-4B\\cos 2x"
Put founded derivatives in the differential equation:
"-4A\\sin 2x-4B\\cos 2x-2(2A\\cos 2x-2B\\sin 2x)+2(A\\sin 2x+B\\cos 2x)=\\sin 2x"
"(-4A+4B+2A)\\sin 2x+(-4B-4A+2B)\\cos 2x=\\sin 2x"
"(-2A+4B)\\sin 2x+(-4A-2B)\\cos 2x=\\sin 2x"
Equating the corresponding coefficients, we obtain a system of equations:
"\\begin{cases} -2A+4B=1\\\\ -4A-2B=0 \\end{cases}"
"\\begin{cases} -2A+4B=1\\\\ B=-2A \\end{cases}"
"\\begin{cases} -10A=1\\\\ B=-2A \\end{cases}"
"\\begin{cases} A=-\\frac{1}{10}\\\\ B=\\frac{1}{5} \\end{cases}"
Finally, the solution of the differential equation is the following:
"y(x)=e^x(C_1\\cos x+C_2\\sin x)-\\frac{1}{10}\\sin 2x+\\frac{1}{5}\\cos 2x."
Comments
Leave a comment